EFEKTIVITAS STRATEGI PETA PIKIRAN (MIND MAP) DALAM PEMBELAJARAN MATEMATIKA DI KELAS VIII SMP NEGERI 6 KOTABARU - Abi Sara (STKIP Paris Barantai, 2017)
Abstract The purpose of this research is (1) Applying mind map strategy to learning mathematics material of tangent of circle, (2) To know the result of student learning through applying mind map strategy on learning mathematics material of tangent of circle, (3) Knowing the effectiveness of the implementation of mind map strategy in learning mathematics in class VIII SMP Negeri 6 Kotabaru. The subjects in this study were students of class VIII SMP Negeri 6 Kotabaru. The method used in this study was an experimental method using non-equivalent control group design, with two classes of control classes and experimental class experimental class using mind map strategy and control class using conventional strategy. Data analysis using comparative statistical technique with two sample t test. The effectiveness of strategy implementation is analyzed through the improvement of learning outcomes. This increase is an increase from the pretest value to the posttest.The results showed: 1) mind maps applied in the experimental class, making the students trained to create and present their own mind map results. making it easier to remember lessons. This is because students have new techniques in making a summary of the lesson. 2) student learning outcomes after analyzed using comparative statistical technique with t test two samples there was no significant difference. The experimental class has an average grade of 79.15 and the control class has an average rating of 74.20. Percentage increase from pretest to posttest by 2.7% for control class and 7.15% for experimental class. 3) based on some results in the research, the learning in the experimental class is better when compared with the learning in the control class. Nevertheless, however, in the drawing conclusions by looking at the results of analysis with comparative statistics with t test two samples as a reference. The conclusion is that there is no significant difference between the control class and the experimental class because the test value of thitung <ttable is 1.53631 <1.68595. Keywords: Effectiveness, MindMap, Circles tangents and Learning Outcomes abstrak